Shifted Selectivity in Protonation Enables the Mild Deuteration of Arenes Through Catalytic Amounts of Bronsted Acids in Deuterated Methanol - Fischer, Oliver; Hubert, Anja; Heinrich, Markus (Journal of Organic Chemistry, 2020)
Taking advantage of the "differentiating effect" of the solvent methanol, deuterations of electron-rich aromatic systems can be carried out under mild acid catalysis and thus under far milder conditions than known so far. The exceptional functional group tolerance observed under the optimized conditions, which even includes highly acid-labile groups, results from a hitherto unexploited shifted selectivity in protonation, and enabled simple and straightforward access to complex deuterium-labeled compounds.
CRIS-Team WoS Importer:2020-10-23